2017
DOI: 10.1016/j.ejor.2017.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical optimization approaches for facility layout problems: The state-of-the-art and future research directions

Abstract: Facility layout problems are an important class of operations research problems that has been studied for several decades. Most variants of facility layout are NP-hard, therefore global optimal solutions are difficult or impossible to compute in reasonable time. Mathematical optimization approaches that guarantee global optimality of solutions or tight bounds on the global optimal value have nevertheless been successfully applied to several variants of facility layout. This review covers three classes of layou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(67 citation statements)
references
References 91 publications
(191 reference statements)
0
59
0
8
Order By: Relevance
“…Francis and White, (1974) provided a comprehensive guide to the facility layout and problem for production facilities analyzing material flows, storage, location, networks, single and multi-planar problems. (Anjos and Vieira, 2017) reviewed three main facility layout problems: row layout, unequal-areas layout, and multifloor layout. They proposed a general formulation for multifloor layout summarize that symmetry remains a key problem in facility layout problems.…”
Section: Literature Review Of Layout Optimizationmentioning
confidence: 99%
“…Francis and White, (1974) provided a comprehensive guide to the facility layout and problem for production facilities analyzing material flows, storage, location, networks, single and multi-planar problems. (Anjos and Vieira, 2017) reviewed three main facility layout problems: row layout, unequal-areas layout, and multifloor layout. They proposed a general formulation for multifloor layout summarize that symmetry remains a key problem in facility layout problems.…”
Section: Literature Review Of Layout Optimizationmentioning
confidence: 99%
“…A Tabu Search (TS) determines the relative location of departments, while mathematical programming calculates their exact location and shape. More research works related to FLP using mathematical optimization can be found in Anjos & Vieira (2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ağırlıklı toplama yöntemi kullanılarak modellenen çok amaçlı optimizasyon problemlerinde normalizasyon işlemi, amaç fonksiyonlarının pareto optimal set içerisinde değişen aralığı kullanılarak yapıldığında, en iyi normalizasyon sonuçlarını vermektedir [15]. Amaç fonksiyonu Grodzevich'in [15] çalışmasında gösterdiği şekilde normalize edilmiştir. Bu durumda normalize edilmiş yeni amaç fonksiyonu z N (25) numaralı denklem kullanılarak elde edilmiştir.…”
Section: Uygulamaunclassified